Application of Contextual Learning in Hadith Lessons and its Application in Society - Imron, Muhammad Al; Yanti, Yuli; Syafe'i, Imam; Hadiati, Eti; Rahmatika, Ratu Vina (ANDRAGOGI, 2025)
Learning hadith in schools is often theoretical and only focuses on memorizing texts, making it difficult for students to understand the values of hadith. This study aims to analyze the application of Islamic Religious Education (PAI) teaching through contextual learning or Contextual Teaching and Learning (CTL) on hadith material in class, and how classroom learning can be applied in everyday life. The research method used is a qualitative method with a library research approach. Data collection techniques are carried out by collecting, reviewing, and analyzing various sources of literature that are relevant to the research topic. The data that has been collected will be analyzed using content analysis techniques with the steps of selecting data, presenting data, and drawing conclusions. The results of the study indicate that contextual learning is effective in improving students' understanding of hadith and encouraging students to apply the teachings of hadith in social interactions in and outside the classroom. Through this approach, students are able to understand the text of hadith theoretically and practically. This paper develops a conceptual framework from previous studies on the implementation of a contextual approach in Islamic education. And offers a recommendation for educators to optimize the effectiveness of the learning process. Thus, this study contributes to improving the quality of Islamic education in terms of affective, social, and cognitive.